A systematic review of childhood maltreatment assessments in population-representative surveys since 1990. - Wendy Hovdestad; Aimée Campeau; Dawn Potter; Lil Tonmyr (PLoS ONE, 2015)
Background Population-representative surveys that assess childhood maltreatment and health are a valuable resource to explore the implications of child maltreatment for population health. Systematic identification and evaluation of such surveys is needed to facilitate optimal use of their data and to inform future research. Objectives To inform researchers of the existence and nature of population-representative surveys relevant to understanding links between childhood maltreatment and health; to evaluate the assessment of childhood maltreatment in this body of work. Methods We included surveys that: 1) were representative of the non-institutionalized population of any size nation or of any geopolitical region ≥ 10 million people; 2) included a broad age range (≥ 40 years); 3) measured health; 4) assessed childhood maltreatment retrospectively; and 5) were conducted since 1990. We used Internet and database searching (including CINAHL, Embase, ERIC, Global Health, MEDLINE, PsycINFO, Scopus, Social Policy and Practice: January 1990 to March 2014), expert consultation, and other means to identify surveys and associated documentation. Translations of non-English survey content were verified by fluent readers of survey languages. We developed checklists to abstract and evaluate childhood maltreatment content. Results Fifty-four surveys from 39 countries met inclusion criteria. Sample sizes ranged from 1,287-51,945 and response rates from 15%-96%. Thirteen surveys assessed neglect, 15 emotional abuse; 18 exposure to family violence; 26 physical abuse; 48 sexual abuse. Fourteen surveys assessed more than three types; six of these were conducted since 2010. In nine surveys childhood maltreatment assessments were detailed (+10 items for at least one type of maltreatment). Seven surveys' assessments had known reliability and/or validity. Conclusions and implications Data from 54 surveys can be used to explore the population health relevance of child maltreatment. Assessment of childhood maltreatment is not comprehensive but there is evidence of recent improvement.